Formulasi dan Evaluasi Sediaan Pelembab Bibir (Lip Balm) Menggunakan Ekstrak Kulit Nanas (Ananas Comomus L. Merr). - vonny kurnia utama; Deri Islami; Nining Sundary (LPPM Universitas Abdurrab, 2023)
Pineapple peel waste is not utilized properly, but which of ingredients such as vitamin C and flavonoid. It can be used as cosmetic ingredients such as lip balm preparations. The purpose of this study was to find out the good pineapple peel extract lip balm. The pineapple peel extract was formulated in the form of lip balm using various concentrations of pineapple peel extract 1, 2, and 3% evaluating the good physical properties of the lip balm preparation. The evaluation of lip balm were evaluated in formulation of organoleptic, melting point, homogenity, pH, spread ability and iritasion. Results showed that the testing each achieved good. The homogeneity test shows that each preparation is homogeneous. The pH of F1, F2, and F3 were fulfilled in at a range 4,5-6,5. The spread ability of F1, F2 and F3 were 5.34, 6.2 and 5.74, respectively. The melting point of each preparation melts well. Lip balm obtaind not cause irritation to the skin. The best formula were F2 at concentration of 2% because it had a texture that is not too hard, had a good pH and had good spread ability.